Dissolved iron release by sediment and dust particles in Antarctic seawater greater than glacial flour and sea-ice particles - Matthew Corkill; Klaus Martin Meiners; Pat Wongpan; Pier van der Merwe; Layla Creac'h; Sandrin Feig; Talitha Nelson; Abigail Jessica Rose Smith; Ashley T. Townsend; Samantha Twiname; Delphine Lannuzel (Marine Chemistry, 2025)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Identifying potential sources of iron-binding ligands in coastal Antarctic environments and the wider Southern Ocean - Abigail J.R. Smith; Talitha Nelson; Lavenia Ratnarajah; Cristina Genovese; Karen Westwood; Thomas M. Holmes; Matthew Corkill; Ashley T. Townsend; Elanor Bell; Kathrin Wuttig; Delphine Lannuzel (Frontiers in Marine Science, 2022)
The availability of iron (Fe) to marine microbial communities is enhanced through complexation by ligands. In Fe limited environments, measuring the distribution and identifying the likely sources of ligands is therefore central to understanding the drivers of marine productivity. Antarctic coastal marine environments support highly productive ecosystems and are influenced by numerous sources of ligands, the magnitude of which varies both spatially and seasonally. Using competitive ligand exchange adsorptive cathodic stripping voltammetry (CLE-AdCSV) with 2-(2-thiazolylazo)- p -cresol (TAC) as a competing artificial ligand, this study investigates Fe-binding ligands (FeL) across the continental shelf break in the Mertz Glacier Region, East Antarctica (64 - 67°S; 138 - 154°E) during austral summer of 2019. The average FeL concentration was 0.86 ± 0.5 nM Eq Fe, with strong conditional stability constants (Log K FeL ) averaging 23.1 ± 1.0. The strongest binding ligands were observed in modified circumpolar deep water (CDW), thought to be linked to bacterial Fe remineralisation and potential siderophore release. High proportions of excess unbound ligands (L’) were observed in surface waters, as a result of phytoplankton Fe uptake in the mixed layer and euphotic zone. However, FeL and L’ concentrations were greater at depth, suggesting ligands were supplied with dissolved Fe from upwelled CDW and particle remineralisation in benthic nepheloid layers over the shelf. Recent sea-ice melt appeared to support bacterial production in areas where Fe and ligands were exhausted. This study is included within our newly compiled Southern Ocean Ligand (SOLt) Collection, a database of publicly available Fe-binding ligand surveys performed south of 50°S. A review of the SOLt Collection brings attention to the paucity of ligand data collected along the East Antarctic coast and the difficulties in pinpointing sources of Fe and ligands in coastal environments. Elucidating poorly understood ligand sources is essential to predicting future Fe availability for microbial populations under rapid environmental change.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.